A Pathological Study Using 2014 WHO Criteria Reveals Poor Prognosis of Grade 3 Ovarian Endometrioid Carcinomas - SOYAMA, HIROAKI (In Vivo, 2018)
Background/Aim: The purpose of this study was to compare the clinical behavior of several grades of endometrioid carcinoma (EC) compared to high-grade serous carcinoma (HGSC), based on World Health Organization 2014 criteria. Materials and Methods: Clinicopathological features were compared between all grades of EC and HGSC, and between HGSC and either grade 1/2 or grade 3 EC. Results: Sixty-five patients with EC and 214 with HGSC were identified. Among patients with EC, 56 displayed 1/2 EC and nine had grade 3 EC. The progression-free (PFS) and overall (OS) survival of patients with grade 1/2 EC were better than of those of patients with HGSC; however, PFS and OS did not statistically differ between patients with grade 3 EC and those with HGSC. Grade 1/2 EC, but not grade 3, was a better prognostic factor compared with HGSC. Conclusion: A grading system for EC would be beneficial for the accurate prognosis of ovarian cancer.